2021
DOI: 10.3389/fimmu.2021.742822
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cystatin C in Human Macrophages Improves Anti-Mycobacterial Immune Responses to Mycobacterium tuberculosis Infection and Coinfection With HIV

Abstract: Tuberculosis owes its resurgence as a major global health threat mostly to the emergence of drug resistance and coinfection with HIV. The synergy between HIV and Mycobacterium tuberculosis (Mtb) modifies the host immune environment to enhance both viral and bacterial replication and spread. In the lung immune context, both pathogens infect macrophages, establishing favorable intracellular niches. Both manipulate the endocytic pathway in order to avoid destruction. Relevant players of the endocytic pathway to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…However, some studies have shown the relationship between cystatin C and infection. Pires et al [24] demonstrated that cystatin C could treat mycobacterium tuberculosis infection by modulating macrophage immune response. In addition, the study by Pikula et al [25] showed that cystatin C had good antibacterial activity against Gram-positive bacteria, including multidrug-resistant bacteria, with high safety and could be considered a new antibacterial drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown the relationship between cystatin C and infection. Pires et al [24] demonstrated that cystatin C could treat mycobacterium tuberculosis infection by modulating macrophage immune response. In addition, the study by Pikula et al [25] showed that cystatin C had good antibacterial activity against Gram-positive bacteria, including multidrug-resistant bacteria, with high safety and could be considered a new antibacterial drug.…”
Section: Discussionmentioning
confidence: 99%
“…CTS mediate the destruction of theses pathogens due to their proteolytic activity at low pH, within the reducing environment of endolysosomes ( 26 ). It is not surprising that intracellular pathogens evolved virulence determinants to subvert the microbicidal mechanisms mediated by endolysosomal CTS as is the case for Mycobacterium tuberculosis ( 27 29 ), as well as for Salmonella, Brucella, Legionella or Chlamydia ( 30 33 ) or Francisella novicida ( 34 ). Autophagy intercepts the endolysosomal pathway ( 34 36 ) and may drive free cytosolic pathogens for destruction in lysosomes ( 37 ) or pathogens contained in vesicles ( 25 , 38 ); both processes involving their entrapment in septin cages ( 39 ).…”
Section: Cathepsins In the Endocytic Pathwaymentioning
confidence: 99%
“…Furthermore, MHC class II requires CTS mediated proteolysis for degradation of the invariant chain (Ii) that blocks MHC class II molecule peptide binding site ( 62 , 63 ). CTSs S, F, and L are cysteine proteases particularly implicated in these processes, with Cts S and F major players in in APCs and the last in thymocytes ( 29 , 42 , 64 67 ). CTS have also been shown to generate antigenic peptide motifs that favor particular T lymphocyte polarization, such as Th2 to Th1, in a mouse model of leishmaniasis ( 68 ).…”
Section: Cathepsins In the Endocytic Pathwaymentioning
confidence: 99%
“…In recent years, our group has been devoted to investigating the involvement of lysosomal cathepsins during host Mtb interactions and their relevance during innate and adaptive immune responses [ 14 , 15 , 16 , 17 , 18 ]. Cathepsins are major players integrated into most processes associated with the lysosome [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that during the infection of human macrophages, Mtb manipulates cathepsins, inducing a general downregulation of gene expression in parallel with a decreased protease activity, either in resting M0 or M1 proinflammatory polarized macrophages [ 14 ]. Relevant targets to manipulate the proteolytic activity of cathepsins include microRNAs [ 28 ], namely miR-106b-5p targeting cathepsin S [ 15 ], and cathepsin natural inhibitors, such as cystatin C [ 16 ]. Recently, we found that another protease inhibitor used in antiretroviral therapy for HIV infection, saquinavir [ 29 ], not only inhibits the viral protease, compromising the maturation and infectivity of new viral particles, but is also able to activate the bulk of cathepsin proteolytic activity during Mtb infection of macrophages [ 18 ].…”
Section: Introductionmentioning
confidence: 99%